2017
DOI: 10.1021/acs.jafc.7b00197
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of 1-Phenylethane-1-thiol as the Character Impact Aroma Compound in Curry Leaves and Its Behavior during Tissue Disruption, Drying, and Frying

Abstract: The most odor-active compounds previously identified by application of an aroma extract dilution analysis were quantitated in freshly picked curry leaves, either by stable isotope dilution assays in combination with GC-GC-MS or by GC-FID after simultaneous extraction/fractionation. Odor activity values (OAVs) were calculated as ratios of concentrations to odor threshold values. The topmost OAVs were obtained for (3Z)-hex-3-enal (grassy; OAV 180 000), (1S)-1-phenylethane-1-thiol (sulfury, burnt; OAV 150 000), (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…( 2 H 2 )-1,8-Cineole (1,3,3-trimethyl­(5,6- 2 H 2 )-2-oxabicyclo­[2.2.2]­octane (( 2 H 2 )- 10 ), 4-( 13 C)­methyl-4-sulfanyl­(1,3,5- 13 C 3 )­pentan-2-one (( 13 C 4 )- 17 ), (3 E ,5 Z )-(10,10,11,11- 2 H 4 )­undeca-1,3,5-triene (( 2 H 4 )- 18 ), ( 2 H 2 )­linalool (3,7-dimethyl­(1,2- 2 H 2 )­octa-1,6-dien-3-ol (( 2 H 2 )- 24 ), and ( 2 H 2 )­geraniol ((2 E )-3,7-dimethyl­(1,1- 2 H 2 )­octa-2,6-dien-1-ol (( 2 H 2 )- 37 ), were synthesized as detailed in the literature. ( 2 H 5 )­Ethyl 2-methylpropanoate (( 2 H 5 )- 1 ), ( 2 H 3 )­methyl 2-methylbutanoate (( 2 H 3 )- 3 ), (2,2,2- 2 H 3 )­ethyl 2-methylbutanoate (( 2 H 3 )- 4 ), and (3,3,3- 2 H 3 )­propyl 2-methylbutanoate (( 2 H 3 )- 7 ) were synthesized from the respective alcohols and carboxylic acids (all Sigma-Aldrich) using the approach detailed above for the synthesis of isotopically unmodified 7 .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…( 2 H 2 )-1,8-Cineole (1,3,3-trimethyl­(5,6- 2 H 2 )-2-oxabicyclo­[2.2.2]­octane (( 2 H 2 )- 10 ), 4-( 13 C)­methyl-4-sulfanyl­(1,3,5- 13 C 3 )­pentan-2-one (( 13 C 4 )- 17 ), (3 E ,5 Z )-(10,10,11,11- 2 H 4 )­undeca-1,3,5-triene (( 2 H 4 )- 18 ), ( 2 H 2 )­linalool (3,7-dimethyl­(1,2- 2 H 2 )­octa-1,6-dien-3-ol (( 2 H 2 )- 24 ), and ( 2 H 2 )­geraniol ((2 E )-3,7-dimethyl­(1,1- 2 H 2 )­octa-2,6-dien-1-ol (( 2 H 2 )- 37 ), were synthesized as detailed in the literature. ( 2 H 5 )­Ethyl 2-methylpropanoate (( 2 H 5 )- 1 ), ( 2 H 3 )­methyl 2-methylbutanoate (( 2 H 3 )- 3 ), (2,2,2- 2 H 3 )­ethyl 2-methylbutanoate (( 2 H 3 )- 4 ), and (3,3,3- 2 H 3 )­propyl 2-methylbutanoate (( 2 H 3 )- 7 ) were synthesized from the respective alcohols and carboxylic acids (all Sigma-Aldrich) using the approach detailed above for the synthesis of isotopically unmodified 7 .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…α‐pinene, sabinene, ẞ‐pinene, 1‐phenylethanethiol, linalool‐like odorants with flavor dilution (FD) factors majorly contribute to the aroma of curry leaves (Verma et al., 2012 ). The unique sulfur and burnt odor is a result of 1‐phenylethanethiol in combination with its high FD factor (Steinhaus, 2017 ). Its ability to produce a strong aroma and flavor is beneficial in terms of using CLP as a condiment in many food applications and preparations.…”
Section: Resultsmentioning
confidence: 99%
“…T1, T2, T3, and T4 contain varying levels of dried CLP w/v = 0% (control), 0.15%, 0.2%, and 0.25%, respectively F I G U R E 3 Variation of sensory properties in cream cheese with varying levels of CLP incorporations. T1, T2, T3, and T4 contain varying levels of dried CLP w/v = 0% (control), 0.15%, 0.2%, and 0.25%, respectively result of 1-phenylethanethiol in combination with its high FD factor (Steinhaus, 2017). Its ability to produce a strong aroma and flavor is beneficial in terms of using CLP as a condiment in many food applications and preparations.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…Herbs and spices, edible oils and other cooking ingredients are a source of flavour for food preparation and/or consumption. GC×GC and MDGC were applied to the analysis of these products, including coriander [50,51,52], curry leaves [53], dried fennel seeds [54], ginger [55], virgin olive oil [56], rapeseed oil [57,58], vinegar [59], tomato-onion puree [60] and truffles [61,62].…”
Section: Foodmentioning
confidence: 99%
“…Curry leaf aroma compounds and odour activity values were assessed by Steinhaus [53], using a MDGC system. The study confirmed that 1-phenylethane-1-thiol (sulfury/burnt notes) is the main impacting aroma compound present in the leaves and that the formation of other odorants, such as (3 Z )-hex-3-enal, (3 Z )-hex-3-en-1-ol (grassy notes) and (2 E ,6 Z )-nona-2,6-dienal (citric notes) can be increased by enzymatic processes unleashed after the leaf tissue was disrupted.…”
Section: Foodmentioning
confidence: 99%